Coronary Artery Disease in Patients Presenting With Acute Ischemic Stroke or Transient Ischemic Attack and Elevated Troponin Levels - Kruska, Mathieu; Kolb, Anna; Fastner, Christian; Mildenberger, Iris; Hetjens, Svetlana; Kittel, Maximilian; Bail, Kathrin; Behnes, Michael; Akin, Ibrahim; Borggrefe, Martin; Szabo, Kristina; Baumann, Stefan (Frontiers in Neurology, 2022)
Background: There is little information concerning the invasive coronary angiography (ICA) findings of patients with acute ischemic stroke (AIS) or transient ischemic attack (TIA) with elevated troponin levels and suspected myocardial infarction (MI). This study analyzed patient characteristics associated with ICA outcomes. Methods: A total of 8,322 patients with AIS or TIA, treated between March 2010 and May 2020, were retrospectively screened for elevated serum troponin I at hospital admission. Patients in whom ICA was performed, due to suspected type 1 MI based on symptoms, echocardiography, and ECG, were categorized according to ICA results (non-obstructive coronary artery disease (CAD): ≥1 stenosis ≥50% but no stenosis ≥80%; obstructive CAD: any stenosis ≥80% or hemodynamically relevant stenosis assessed by FFR/iwFR). Results: Elevated troponin levels were detected in 2,205 (22.5%) patients, of whom 123 (5.6%) underwent ICA (mean age 71 ± 12 years; 67% male). CAD was present in 98 (80%) patients, of whom 51 (41%) were diagnosed with obstructive CAD. Thus, ICA findings of obstructive CAD accounted for 2.3% of patients with troponin elevation and 0.6% of all stroke patients. The clinical hallmarks of myocardial ischemia, including angina pectoris (31 vs. 15%, p < 0.05) and regional wall motion abnormalities (49 vs. 32%, p = 0.07), and increased cardiovascular risk indicated obstructive CAD. While there was no association between lesion site or stroke severity and ICA findings, causal large-artery atherosclerosis was significantly more common in patients with obstructive coronary disease (p < 0.05). Conclusion: The rate of obstructive CAD in patients with stroke or TIA and elevated troponin levels with suspected concomitant type I MI is low. The cumulation of several cardiovascular risk factors and clinical signs of MI were predictive. AIS patients with large-artery atherosclerosis and elevated troponin may represent an especially vulnerable subgroup of stroke patients with risk for obstructive CAD.